Research Trends in Teacher Digital Competencies: A Bibliometric Review - Senita Butar Butar; Respita Haniva; Hari Mulyadi (Jurnal VARIDIKA, 2024)
Teacher digital competence (TDC) is a pivotal skill in 21st-century education, essential for addressing the extensive educational demands of the digital age and technological advancements. This study aims to investigate and evaluate research trends in teacher digital competency from 2013 to 2023 using descriptive bibliometric analysis. Researchers utilized the Scopus database for data collection, following a four-stage process to obtain 235 publications. These publications were then analyzed using the VOS Viewer software. The findings of this study are as follows: 1) The research trend on TDC has shown a continuous increase from 2013 to 2020; 2) Citation trends peaked in 2018, with the work of Gudmundsdottir and Hatlevik (2018) being the most frequently cited; 3) Spain emerged as the leading country in this field, with 100 publications and five international collaborations; 4) Research on teacher digital competence primarily focuses on digital competence itself, higher education, ICT, digital technology, digital e-learning, personnel training, educational technology, digital devices, digital resources, teaching and learning, motivation, digital skills, digital literacy, TPACK, information and communication technologies, professional development, professional digital competence, self-assessment, education, and teacher professional development. Recent themes such as digital teaching competence, improvement, and digital tools are recommended for further research on teacher digital competence.